Anatomical Variations of Renal Vessels- A Cadaveric Study with Clinical Relevance - Dr Amudalapalli S Narayana; Dr Kiran Kumar P; Dr Anitha T (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Blood supply to the kidneys is characterized by more frequent presence of variations in arteries and veins supplying them. Normally each kidney is supplied by single renal artery and drained by single renal vein. Variation in the number, origin, pathway and branching pattern of renal arteries is common. Frequently seen anatomical variation is additional renal artery. Aim: To identify the presence of variations of renal vessels in the human cadavers. Material and methods: An observational cadaveric study was conducted on 80 kidneys from 40 formalin-fixed human cadavers from 2019 to 2025 in the Department of Anatomy, Chalmeda Anandarao institute of medical sciences, Karimnagar, Telangana, India. The number of cadavers showing variations of renal vessels was determined. Results: The study included 80 kidneys from 40 formalin-fixed human cadavers. Eight (20%) cadavers were found to have variations in renal vessels while 32 (80%) cadavers show presence of single renal vessel going to each kidney. The double renal artery variations were present bilaterally in 01 (2.5%) cadaver and aberrant renal artery in 02 (5%) cadavers but both are in left side. The superior polar artery was present in 01 (2.5%) cadaver right side and inferior polar artery was present in 01 (2.5%) cadaver left side. Early divisions of renal artery were present in 2 (5%) cadavers. Accessory renal vein were present in right side 1 (2.5%) cadaver. Conclusion: Variations of renal vessels supplying to the kidneys it is necessary to have prior knowledge of them as now a day’s more number of patients is undergoing renal transplants, angiography procedures. The knowledge of these variations is also useful for treatment of renal trauma and tumors.